Life is in the air: An expedition into the Amazonian atmosphere - Mota de Oliveira, Sylvia; Duijm, Elza; Stech, Michael; Ruijgrok, Jasmijn; Polling, Marcel; Barbosa, Cybelli G. G.; Cerqueira, Gabriela R.; Nascimento, Antônio H. M.; Godoi, Ricardo H. M.; Taylor, Philip E.; Wolff, Stefan; Weber, Bettina; et al. (Frontiers in Ecology and Evolution, 2022)
Biological particles suspended in the atmosphere have a crucial role in the dynamics of the biosphere underneath. Although much attention is paid for the chemical and physical properties of these particles, their biological taxonomic identity, which is relevant for ecological research, remains little studied. We took air samples at 300 meters above the forest in central Amazonia, in seven periods of seven days, and used high-throughput DNA sequencing techniques to taxonomically identify airborne fungal and plant material. The use of a molecular identification technique improved taxonomic resolution when compared to morphological identification. This first appraisal of airborne diversity showed that fungal composition was strikingly different from what has been recorded in anthropogenic regions, with tenfold lower percentage of allergenic fungi and crop pathogens. Plant composition was a combination of mainly Amazonian taxa, with some extra-Amazonian, predominantly wind pollinated, families. Finally, the detection of three bryophyte genera feeds the debate about the role of long distance dispersal in the distribution of these plants.